Cyp2c44 Gene Disruption Exacerbated Pulmonary Hypertension and Heart Failure in Female but Not Male Mice. (September 2016) - Joshi, Sachindra Raj; Lakhkar, Anand; Dhagia, Vidhi; Zias, Ariadne L.; Soldatos, Vasiliki; Oshima, Kaori; Jiang, Houli; Gotlinger, Katherine; Capdevila, Jorge H.; Schwartzman, Michal L.; McMurtry, Ivan F.; Gupte, Sachin A.
Epoxyeicosatrienoicacids (EETs), synthesized from arachidonic acid by epoxygenases of the CYP2C and CYP2J gene subfamilies, contribute to hypoxic pulmonary vasoconstriction (HPV) in mice. Despite their roles in HPV, it is controversial whether EETs mediate or ameliorate pulmonary hypertension (PH). A recent study showed that deficiency of Cyp2j did not protect male and female mice from hypoxia-induced PH. Since CYP2C44 is a functionally important epoxygenase, we hypothesized that knockout of the Cyp2c44 gene would protect both sexes of mice from hypoxia-induced PH. We tested this hypothesis in wild-type (WT) and Cyp2c44 knockout ( Cyp2c44 −/− ) mice exposed to normoxia (room air) and hypoxia (10% O2 ) for 5 weeks. Exposure of WT and Cyp2c44 −/− mice to hypoxia resulted in pulmonary vascular remodeling, increased pulmonary artery resistance, and decreased cardiac function in both sexes. However, in female Cyp2c44 −/− mice, compared with WT mice, (1) pulmonary artery resistance and right ventricular hypertrophy were greater, (2) cardiac index was lower, (3) left ventricular and arterial stiffness were higher, and (4) plasma aldosterone levels were higher, but (5) there was no difference in levels of EET in lungs and heart. Paradoxically and unexpectedly, we found that Cyp2c44 disruption exacerbated hypoxia-induced PH in female but not male mice. We attribute exacerbated PH in female Cyp2c44 −/− mice to elevated aldosterone and as-yet-unknown systemic factors. Therefore, we suggest a role for the human CYP2C genes in protecting women from severe PH and that this could be one of the underlying causes for a better 5-year survival rate in women than in men.